Analysis of Notarial Debt Agreement Deeds And Their Relation To Unlawful Acts In Decision No. 211/PDT.G/2021/PN.SKT - Rahmawati Febriana Kartikasari; Yudho Taruno. M; Diana Lukitasari (International Journal of Educational Research & Social Sciences, 2026)
This study examines the legal characteristics of unlawful acts arising from debt agreement deeds prepared before a notary, with particular reference to the Surakarta District Court Decision No. 211/Pdt.G/2021/PN.Skt. It also explores the legal considerations adopted by the panel of judges in resolving the dispute. The issue addressed in this study stems from a debt agreement dispute that was not limited to breach of contract but also involved elements of unlawful conduct, particularly because the disputed acts were considered inconsistent with good faith, propriety, and the proper use of authentic deeds. This research adopts a normative legal method using statutory and case approaches. The legal materials analyzed consist of primary, secondary, and tertiary legal sources, which were examined qualitatively. The findings reveal that the dispute fulfilled the elements of an unlawful act as stipulated under Article 1365 of the Indonesian Civil Code, namely the existence of an unlawful act, fault, loss, and a causal relationship between the act and the damage suffered. The case demonstrates that a contractual relationship may evolve into an unlawful act when one party suffers harm due to the misuse of a notarial deed that is not based on good faith. The judges’ reasoning was primarily grounded in the proof of material loss and the conduct of the parties, which was deemed contrary to law, fairness, and propriety. This study offers a legal contribution by emphasizing that a notarial deed should not be understood solely as an authentic evidentiary instrument, but also as a legal instrument that may give rise to liability when it is used unlawfully.